Leveraging the entrepreneurship talents based on Prophet Muhammad’s business acumen: The case of akademi bakat ABS - Suhaili Ikhsan; Nur Husna Abd Wahid; Nor Hidayah Mustafa (Institute of Advanced Engineering and Science, 2020)
Realizing that each human being is naturally gifted with numerous talents, the Akademi Bakat ABS is set up to uphold this value through its unique curriculum, approach, and eco-system in the school. Till date, 75% of the learning program is based on learning-by-doing approach. The core vision is to nurture the students’ inner-self with the 6 values of entrepreneurship i.e. social intelligence, integrity, altruism, creative and innovative, diplomacy, and righteousness since pre-school and hence, leverage the mindset, behaviour, and subsequently the cultural value of entrepreneurship among the students. With the aim to be an alternative school that will confront the future education, particularly in view of the Malaysian education landscape, the philosophy lies in the concept of being an independent thinker rather than consumer thinker. Only then, the element of creative thinking can be cultivated which is crucial in economic development as well as novel development in terms of technologies, products, and systems. Akademi Bakat ABS believed, with all the virtues it holds, the possibility to overcome on the overwhelmed issue of graduates’ unemployability and incompetency in human skill can be achieved in all respect especially in confronting the Industrial Revolution 4.0 agenda. Finally, with support from each segment of the society (students, teachers, parents, ministry, industries, etc.), Akademi Bakat ABS sees itself as an industrial player that can holistically benefit the Malaysian education eco-system.